1978
DOI: 10.1364/ao.17.002381
|View full text |Cite
|
Sign up to set email alerts
|

Self-holograms of laser-induced surface depressions in heavy hydrocarbons

Abstract: Among applications of lasers in the petroleum industry are samples of heavy oils heated by a He-Ne laser beam. It is shown that laser power concentrations as low as 1 mW/mm(2) induce noticeable changes in the form of the surface. The far-field diffraction pattern of the reflected wave can be considered as a self-hologram of the hole, with the paraxial focus of the bottom of the hole as a point reference source. Annular images corresponding to different zones of the hole are reconstructed by illuminating the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…1k, 1m and 1n) (2,3,10,14). We note that the magnitude of this effect is qualitatively different than previously reported surface depressions, which were too weak to be directly observed by the naked eye or ordinary photography (10,(17)(18)(19)(20)(21). To understand these distinct deformations between deep and shallow liquids, we varied the liquid layer thickness while keeping the laser beam the same.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…1k, 1m and 1n) (2,3,10,14). We note that the magnitude of this effect is qualitatively different than previously reported surface depressions, which were too weak to be directly observed by the naked eye or ordinary photography (10,(17)(18)(19)(20)(21). To understand these distinct deformations between deep and shallow liquids, we varied the liquid layer thickness while keeping the laser beam the same.…”
Section: Introductionmentioning
confidence: 64%
“…More rigorous theoretical treatments (9)(10)(11)(12)(13)(14)(15)(16) and controlled experiments (10,(17)(18)(19)(20)(21) were performed later with non-uniform surface tension created by either substrate heating or surface radiative heating. Besides these fundamental investigations, more cases have been investigated in enormous applications involving liquids or soft matters such as lithography and 3D printing (22)(23)(24), heat transfer and mass transport (19), crystal growth and alloy welding (25,26), dynamic grating and spatial light modulator (15,27), microfluidics and adaptive optics (19,(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Here, as shown in (2) of Figure 2b, no apparent change in the CCD image was observed. Such surface depression has been reported and explained on the basis of inhomogeneous distribution of surface tension induced by local temperature elevation [14][15]. The authors have also confirmed such phenomena for the glycine and polymer solution layers [11,16].…”
Section: -1 Droplet Formation Of Urea In Unsaturated and Supersaturmentioning
confidence: 53%
“…The quasi-stationary diameter of this ring is called the PTC signal, as shown in Figure 1 c. In fact, the PTC effect can be considered as a particular stage of a more general concentration-capillary effect, which was discovered by Bezuglyi in 1975 while irradiating the iodine solution with a mercury lamp [ 28 ]. In its classical form, the TC phenomenon was studied in the late 1970s while irradiating heavy oil fractions with a Helium-Neon (He-Ne) laser [ 29 , 30 ]. The PTC signal is called both the diffraction [ 28 ] and interference [ 30 ] patterns.…”
Section: Methodsmentioning
confidence: 99%